Question
upstudy study bank question image url

Use implicit differentiation to find \( \frac{d y}{d x} \) \[ x^{3}+y^{3}=12 x y \]

Ask by Nguyen O'Quinn. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \frac{dy}{dx} = \frac{4y - x^{2}}{y^{2} - 4x} \]

Solution

Find the first order derivative with respect to \( x \) for \( x^{3}+y^{3}=12xy \). Find the first derivative by following steps: - step0: Find the derivative with respect to \(x\): \(x^{3}+y^{3}=12xy\) - step1: Take the derivative: \(\frac{d}{dx}\left(x^{3}+y^{3}\right)=\frac{d}{dx}\left(12xy\right)\) - step2: Calculate the derivative: \(3x^{2}+3y^{2}\frac{dy}{dx}=\frac{d}{dx}\left(12xy\right)\) - step3: Calculate the derivative: \(3x^{2}+3y^{2}\frac{dy}{dx}=12y+12x\frac{dy}{dx}\) - step4: Move the expression to the left side: \(3y^{2}\frac{dy}{dx}-12x\frac{dy}{dx}=12y-3x^{2}\) - step5: Add and subtract: \(\left(3y^{2}-12x\right)\frac{dy}{dx}=12y-3x^{2}\) - step6: Divide both sides: \(\frac{\left(3y^{2}-12x\right)\frac{dy}{dx}}{3y^{2}-12x}=\frac{12y-3x^{2}}{3y^{2}-12x}\) - step7: Divide the numbers: \(\frac{dy}{dx}=\frac{4y-x^{2}}{y^{2}-4x}\) The derivative of \( y \) with respect to \( x \) using implicit differentiation is given by: \[ \frac{dy}{dx} = \frac{4y-x^{2}}{y^{2}-4x} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find \(\frac{dy}{dx}\) using implicit differentiation, we differentiate both sides of the equation \(x^3 + y^3 = 12xy\) with respect to \(x\). Differentiating the left side: \[ \frac{d}{dx}(x^3) + \frac{d}{dx}(y^3) = 3x^2 + 3y^2\frac{dy}{dx} \] Differentiating the right side: \[ \frac{d}{dx}(12xy) = 12\left(x\frac{dy}{dx} + y\right) = 12y + 12x\frac{dy}{dx} \] Now we equate both sides: \[ 3x^2 + 3y^2\frac{dy}{dx} = 12y + 12x\frac{dy}{dx} \] Rearranging the equation to isolate \(\frac{dy}{dx}\): \[ 3y^2\frac{dy}{dx} - 12x\frac{dy}{dx} = 12y - 3x^2 \] Factoring out \(\frac{dy}{dx}\): \[ \frac{dy}{dx}(3y^2 - 12x) = 12y - 3x^2 \] Finally, we solve for \(\frac{dy}{dx}\): \[ \frac{dy}{dx} = \frac{12y - 3x^2}{3y^2 - 12x} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy